1989
DOI: 10.1021/bi00431a024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on phenylalanine hydroxylase from Chromobacterium violaceum. Evidence for the formation of an enzyme-oxygen complex

Abstract: Steady-state kinetic analysis of pterin-dependent phenylalanine hydroxylase from Chromobacterium violaceum indicated that the enzyme follows a partially ordered reaction mechanism. The data suggested that oxygen is the first substrate to bind to the enzyme. This result was further supported by rapid-quench experiments in which the enzyme-oxygen complex was trapped to yield product. Additional support for the presence of an enzyme-oxygen complex was derived from magnetic susceptibility measurements of molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…The kinetic mechanism, which provides a framework for discussion of the order of the individual steps in catalysis, has been determined for TyrH (36) and for the bacterial PheH (37,38). For both enzymes, all three substrates must be bound before catalysis occurs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic mechanism, which provides a framework for discussion of the order of the individual steps in catalysis, has been determined for TyrH (36) and for the bacterial PheH (37,38). For both enzymes, all three substrates must be bound before catalysis occurs.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of rat TyrH, the order is 6-methyltetrahydropterin first, followed by oxygen in rapid equilibrium, and then tyrosine (36). In the case of bacterial PheH, Pember et al (37) reported that oxygen bound first, followed by a random binding of 6,7-dimethyltetrahydropterin and phenylalanine. In contrast, Volner et al (38), using an identical approach, concluded that the binding was ordered and that the order was dimethyltetrahydropterin, phenylalanine, and oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Under such conditions, squared terms can be introduced into the rate equation if an individual term contains the concentrations of more than one substrate, allowing one to determine more readily the relevant steady-state kinetic equation. Such an analysis was carried out for tyrosine hydroxylase using 6-methyltetrahydropterin (Fitzpatrick,199 1 a) and for bacterial PAH using 6,7-dimethyltetrahydropterin (Pember et al, 1989). The results with both enzymes were interpreted in favor of ter-bi sequential mechanisms, but the proposed mechanisms differed in the order of addition of the three substrates (Fig.…”
Section: Recent Mechanistic Studies Of Tyrosine and Tryptophan Hydmentioning
confidence: 99%
“…With bacterial PAH, oxygen was proposed to bind first, followed by random binding of tetrahydropterin and phenylalanine. However, it was noted by Pember et al (1989) that there may be a preferred pathway with tetrahydropterin binding before phenylalanine, because substrate inhibition was seen with the amino acid. If this is the case, the principle difference between the two mechanisms is in the order of binding of oxygen and the tetrahydropterin.…”
Section: Recent Mechanistic Studies Of Tyrosine and Tryptophan Hydmentioning
confidence: 99%
“…The protein was thought to be copper dependent [17,18,19], and later the same researchers claimed that cPAH displays full activity in the absence of a transition metal [20,21,22]. While this work was in progress, Chen and Frey [15] showed that the published sequence [19] for cPAH has a frame shift, and that their isolated cPAH is iron dependent (as are all known AAAHs).…”
Section: Introductionmentioning
confidence: 99%